FAIR+E pathogen data for surveillance and research: lessons from COVID-19 - Neves, Aitana; Cuesta, Isabel; Hjerde, Erik; Klemetsen, Terje; Salgado, David; van Helden, Jacques; Rahman, Nadim; Fatima, Nazeefa; Karathanasis, Nestoras; Zmora, Pawel; Åkerström, Wolmar Nyberg; Grellscheid, Sushma Nagaraja; et al. (Frontiers in Public Health, 2023)
The COVID-19 pandemic has exemplified the importance of interoperable and equitable data sharing for global surveillance and to support research. While many challenges could be overcome, at least in some countries, many hurdles within the organizational, scientific, technical and cultural realms still remain to be tackled to be prepared for future threats. We propose to (i) continue supporting global efforts that have proven to be efficient and trustworthy towards addressing challenges in pathogen molecular data sharing; (ii) establish a distributed network of Pathogen Data Platforms to (a) ensure high quality data, metadata standardization and data analysis, (b) perform data brokering on behalf of data providers both for research and surveillance, (c) foster capacity building and continuous improvements, also for pandemic preparedness; (iii) establish an International One Health Pathogens Portal, connecting pathogen data isolated from various sources (human, animal, food, environment), in a truly One Health approach and following FAIR principles. To address these challenging endeavors, we have started an ELIXIR Focus Group where we invite all interested experts to join in a concerted, expert-driven effort towards sustaining and ensuring high-quality data for global surveillance and research.